(untitled) (Research Nepal Journal of Development Studies, 2023)
Nepal is one of the most beautiful country in between two big countries China and India. It is also known as the third pole of the earth, because of having world’s highest peak Mt. Everest. Culturally it is the land of emblem of peace- Lord Buddha. Furthermore, it is the land of spectacular mesmerizing nature and unique culture among the world. However, it is sacred and mysterious land and still remains to explore thousands of issues. Among them the Ecotourism is one of the prominent issue. Thus to find out the socio economic status of ecotourism with the reference to Khaptad National park the case study on non-participatory approach in data collection have been conducted. Scenic Attraction, Pleasant Climate, Vegetation, Flora and Fauna, Buki Daha, Danfekot, Patan and Panoramic View, Nagdhunga or Lokhada, Khaptad Daha, Khapar Mando, Sahasra Linga, Upper Triveni River, and the Ashram of Khaptad swami are the basic centre of ecotourism in Khaptad Zone.